2008
DOI: 10.2340/16501977-0256
|View full text |Cite
|
Sign up to set email alerts
|

Driving behaviour after brain injury: a follow-up of accident rate and driving patterns 6-9 years post-injury.

Abstract: Patients with traumatic brain injury represent a risk group for accidents post-injury, while those with brain injury after cerebrovascular accidents do not. Possible causes for this difference are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 11 publications
3
36
2
Order By: Relevance
“…There is low level evidence that drivers following stroke have no greater incidence of being involved in a motor vehicle accident or receiving a driving violation than drivers in the general population (Haselkorn, Mueller & Rivara, 1998;Lundqvist, Alinder & Ronnberg, 2008;Schanke, Rike, Molmen & Osten, 2008;Van Zomeren et al, 1987). This may be due to the adoption of compensatory strategies similar to those used by elderly drivers, although there is no direct evidence of this in stroke patients (De Raedt & Ponjaert-Kristoffersen, 2000;Fisk et al, 1997;George, Clark & Crotty, 2006;Unsworth, Wells, Browning, Thomas & Kendig, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is low level evidence that drivers following stroke have no greater incidence of being involved in a motor vehicle accident or receiving a driving violation than drivers in the general population (Haselkorn, Mueller & Rivara, 1998;Lundqvist, Alinder & Ronnberg, 2008;Schanke, Rike, Molmen & Osten, 2008;Van Zomeren et al, 1987). This may be due to the adoption of compensatory strategies similar to those used by elderly drivers, although there is no direct evidence of this in stroke patients (De Raedt & Ponjaert-Kristoffersen, 2000;Fisk et al, 1997;George, Clark & Crotty, 2006;Unsworth, Wells, Browning, Thomas & Kendig, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A Norwegian study conducted longer-term follow-up of 65 patients 6-9 years after stroke to assess accident rates and driving fitness after successful assessment (Schanke et al, 2008). The patients had made considerable changes to their driving patterns from their pre-injury driving, but there was no significant difference in accident rates when compared with national normative data.…”
Section: Introductionmentioning
confidence: 99%
“…Data of the individual studies on the crash rate and severity of TBI among drivers with TBI compared to those who don't have TBI are summarized in Table 1. Only one of these studies (Schanke, et al, 2008) evaluated crash risk adjusted for distance driven, which is possibly the most important potential confounding variable. We independently calculated rate ratios to allow us to combine the data from all four studies that reported the number of events.…”
Section: Direct Evidence For the Impact Of Traumatic Brain Injury On mentioning
confidence: 99%
“…Five studies (Formisano, et al, 2005;Gouvier, et al, 1989;Haselkorn, Mueller, & Rivara, 1998;Schanke, Rike, Molmen, & Osten, 2008;Schultheis, Matheis, Nead, & DeLuca, 2002) attempted to directly determine crash risk among drivers with TBI through evaluation of self-reported crashes or crashes recorded in a state licensing database. Data of the individual studies on the crash rate and severity of TBI among drivers with TBI compared to those who don't have TBI are summarized in Table 1.…”
Section: Direct Evidence For the Impact Of Traumatic Brain Injury On mentioning
confidence: 99%
“…Research findings on the accident risk of drivers after brain injury have been inconsistent, with some reporting no increased risk of accidents (Haselkorn, Mueller, & Rivara, 1998), and some studies reporting a higher accident risk when compared with the general population (Bivona et al, 2012;Schanke, Molmen, & Osten, 2008). This discrepancy in accident rate may be a result of some individuals using compensatory driving strategies (e.g., avoiding night driving), and henceforth reducing the risks that they are exposed to (Labbe, Vance, Wadley, & Novack, 2013).…”
Section: Demands and Moderators Of Drivingmentioning
confidence: 99%